Exploiting SOA within emaintenance - Karim, Ramin; Kajko-Mattsson, Mira; Soderholm, Peter (International Conference on Software Engineering 2008, 2008)
SOA is being exploited in many various business domains. One of them is industrial maintenance. In this paper, we outline an eMaintenance Platform (eMP) for maintaining complex technical systems. This platform is part of the eMaintenance Management Framework (eMMF). Our primary goal is to explore how SOA can be exploited within industrial maintenance. Our secondary goal is to provide eMP as an effective tool for organizations to conduct their maintenance and support.